Third Five Year Plan Madras State, Review of Progress For 1961-62 and Programme for 1962-63 - Planning Commission (Planning Commission, 1962)
The increase in the number of schools, both at the elementary and secondary stages of education during Second Plan period has necessitated the appointment of additional inspecting officers for the efficient inspection of schools. It has become necessary to strengthen the administration staff at all levels not only for inspection of the large number of schools opened in recent years but also to cope with the work involved in the successful implementation of the various Plan schemes. During 1961-62, 3 additional D.E.Os. and 1 Inspectors of Girls Schools were sanctioned.
Finance (Planning and Development) Department Government of Madras